Trust, commitment, and conflict resolution styles as predictors of romantic relationship satisfaction among emerging adults in Malaysia - Wong, Cheng Xiang; Wong, Zi Zheng (2025)
Maintaining good romantic relationships is a critical developmental challenge during emerging adulthood, yet many emerging adults find it difficult to establish long-lasting and happy relationships. This study aims to explore how trust, commitment, and constructive and destructive conflict resolution styles influence relationship satisfaction among emerging adults in Malaysia. A quantitative, cross-sectional design was employed with 98 participants aged 18–25 years, recruited using purposive sampling. The sample comprised 56.1% females (n = 55) and 43.9% males (n = 43), encompassing Malay, Chinese, and Indian ethnicities. Standardized instruments, including the Relationship Assessment Scale (RAS), Dyadic Trust Scale (DTS), Dedication Subscale of Commitment Inventory (CI), and the Conflict Resolution Styles Inventory (CRSI), were administered. Data collection was conducted through online platforms using Qualtrics, and data were analyzed with IBM SPSS version 24. Multiple linear regression analysis revealed that trust (β = .452, p < .001) and commitment (β = .174, p = .049) significantly predicted higher relationship satisfaction, whereas destructive conflict resolution style (β = −.242, p = .004) significantly predicted lower relationship satisfaction. In contrast, constructive conflict resolution style was not a significant predictor (β = .064, p = .446). These findings align with Interdependence Theory, which emphasizes the importance of dependence and correspondence of outcomes in shaping relationship satisfaction. By highlighting the developmental and cultural factors influencing young adults’ relationships in Malaysia, the study contributes to the literature and provides practical implications for relationship education, counseling, and youth development initiatives.